2006
DOI: 10.1103/physrevd.73.044008
|View full text |Cite
|
Sign up to set email alerts
|

Tilted cosmological models of Bianchi type V

Abstract: Cosmological models of Bianchi type V and I containing a perfect fluid with a linear equation of state plus cosmological constant are investigated using a tetrad approach where our variables are the Riemann tensor, the Ricci rotation coefficients and a subset of the tetrad vector components. This set, in the following called S, describes a spacetime when its elements are constrained by certain integrability conditions and due to a theorem by Cartan this set gives a complete local description of the spacetime. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[12] found that 364 of 367 (99·2%) P. falciparum infections, and 325 of 432 (75·2%) P. vivax infections, were diagnosed within 6 months of arrival in the USA. Second, in a similar UK study of imported malaria, 1427 of 1434 (99·5%) P. falciparum and 543 of 829 (65·5%) P. vivax infections occurred within 6 months of arrival in the UK [13]. Available data on diagnoses from Western Australia for the period 1990 -2001 are consistent with these reports in that for P. falciparum , all 85 (100%) infections with falciparum malaria occurred within 6 months of arrival.…”
Section: Incidencementioning
confidence: 54%
See 1 more Smart Citation
“…[12] found that 364 of 367 (99·2%) P. falciparum infections, and 325 of 432 (75·2%) P. vivax infections, were diagnosed within 6 months of arrival in the USA. Second, in a similar UK study of imported malaria, 1427 of 1434 (99·5%) P. falciparum and 543 of 829 (65·5%) P. vivax infections occurred within 6 months of arrival in the UK [13]. Available data on diagnoses from Western Australia for the period 1990 -2001 are consistent with these reports in that for P. falciparum , all 85 (100%) infections with falciparum malaria occurred within 6 months of arrival.…”
Section: Incidencementioning
confidence: 54%
“…The P. vivax sensitivity, in particular, is markedly improved over the 50 -65% reported in previous studies [1,5]. This sensitivity estimate calculated in acute samples is conservative because our proposed policy mandates a 6-month delay before testing, negating the impact of the estimated 7-14 day serological window period observed in early infection [11][12][13].…”
Section: Discussionmentioning
confidence: 81%